The distribution of IT in Europe's rural areas (Objective 1 and 5b), its current state-of-the-art and its potential role for future economic developments: A survey of local actors in Europe's rural areas - Jeanette Muller (European Regional Science Association (ERSA), 1998)
The transformation to an information society has lead to a diminishing importance of proximity as a factor for local economic development. Information technology (IT) is being regarded as one of the most important means for reducing spatial disadvantages, particularly for rural areas. The purpose of this paper is to examine the distribution and the role of IT in Europe's rural areas. Firstly, two overall issues are discussed: (1) the opportunities IT offers for the development in rural spaces, and (2) the use of computing equipment on a local level in rural areas. Secondly, this paper explores these two issues by looking at local authorities / local development agencies who benefit from the Community Initiative LEADER. This study focuses on two aspects: (1) the availability of such facilities in general, and (2) the actual access to information resources such as the Internet. The results of this survey show that -despite of a general trend within local authorities to improve their computing facilities - there is significant variation in the availability between the European regions. Overall, most local actors are confronted with a considerable lack of adequate computing facilities as well as extreme deficiencies in adapting to such facilities. As a consequence, I will point out (1) the necessity of the establishment of such facilities and (2) ways in which IT can those areas to increase their competitiveness and increase their economic potentials. Finally, I will develop a future scenario of IT in Europe's rural areas. Key words: IT, rural development, comparative study.
Keywords: 330